Actividad antiinflamatoria in vitro del extracto etanólico e hidroetanólico de hojas y tallo de Senna quinquangulata - Uraco Mafaldo, Anthony Alejandro (2025)
Senna quinquangulata is a plant preserved in the Loreto region, known for its extensive therapeutic properties in traditional medicine, including promising anti-inflammatory effects. Objective: To determine the anti-inflammatory activity of the ethanolic and hydroethanolic extracts of S. quinquangulata leaves and stems on plasma erythrocytes. Methodology: the leaves and stems were collected and used for the preparation of the alcoholic and hydroalcoholic extracts. The anti-inflammatory activity of these extracts was evaluated at concentrations of 10, 100, and 1000 µg/ml on plasma erythrocytes. Results: none of the evaluated concentrations of S. quinquangulata showed an inhibition rate greater than 50%, resulting in an IC50 > 1000 µg/mL. Conclusion: the tested extracts did not show anti inflammatory activity at the evaluated concentrations.